Bone weathering in a Mediterranean climate region: An experimental case study from Doñana National Park (Spain) - Marcos Pizarro-Monzo; Laura Domingo; Juan José Negro; Enrique Cantero; David M. Martín-Perea; M.Soledad Domingo (PLoS ONE, 2025)
Bone weathering constitutes a highly informative and commonly studied variable in taphonomic analyses. Vertebrate paleontologists, zoo-archeologists and forensic anthropologists have used weathering as a taphonomic clock to ascertain the exposure time of a bone assemblage before burial. Given that climatic conditions largely govern the weathering process, it is essential to investigate the effects of weathering across various climatic settings. This study analyzes the bone weathering process at Doñana National Park (Spain), a Mediterranean climate area. In 2018, we set an experiment in which four bones, three tibias and one skull, belonging to the main ungulates from Doñana (red deer, fallow deer, horse and wild boar) were placed in an enclosure and exposed to the natural environmental conditions. We present here results after almost 6 years of exposure. Over the study period, the most exposed area of the bones reached weathering stages 1 and 2, an intermediate progression between semi-arid tropical savannas, where weathering stages were initially described, and temperate and colder climates. By the final observation, the tibia of the horse, the heaviest taxon in our study, only has reached weathering stage 1, so our study agrees with previous studies in that the rate of weathering differs across body size, being slower in larger animals. The skull of Sus scrofa stands out for exhibiting modifications that differ from those observed in the tibias, probably due to the different structural anatomy of this bone. We have characterized the local meteorological conditions throughout the experiment and the soil composition as they might play a role in the weathering progression. This research constitutes a first attempt to calibrate the weathering scale in a Mediterranean climatic context, a setting that contains abundant and important fossil assemblages but that lacks bone weathering calibration.